Risk of dementia according to smoking cessation after newly diagnosed atrial fibrillation: a nationwide cohort study. (14th October 2021) - Lee, H J; Lee, S R; Choi, E K; Jung, J H; Han, K D; Oh, S I; Lip, G Y H
Abstract: Background: Incident atrial fibrillation (AF) is associated with an increased risk of dementia. There are limited data about the impact of smoking cessation after AF diagnosis on the risk of incident dementia. Purpose: To evaluate the association between changes in smoking status after newly diagnosed AF and the risk of dementia. Methods: Among patients with new-onset AF between 2010 and 2016, those who received a national health checkup exam within 2 years before and after the AF diagnosis were included. Patients who had prevalent dementia were excluded. Subjects were categorized into 4 groups according to the status of smoking before and after AF diagnosis: (1) never smoker; (2) ex-smoker; (3) quit-smoker after AF diagnosis; and (4) current smoker. The primary outcome was incident dementia during follow-up. Results: A total of 126, 252 patients were included (mean age 63, SD 12.0; men 62%; mean CHA2DS2-VASc 2.7). During a median 3 years of follow-up, dementia occurred in 5, 925 patients (1.11 per 1000 person-years [1000PY]) (Alzheimer's dementia 1.5 per 1000 PY and vascular dementia 0.24 per 1000 PY, respectively). Never smokers, ex-smokers, quit-smokers, and current smokers were 52%, 27%, 7%, and 14% of the total study population, respectively. After multivariable adjustment, quit-smokers showed a higher risk of dementia than never smokers (hazard ratio [HR] 1.16, 95% confidence interval [CI] 1.03–1.32), but the risk was significantly decreased when compared to current smokers (HR 0.83, 95% CI 0.72–0.95). Alzheimer's dementia and vascular dementia showed consistent results as main (Figure). Conclusion: All types of smoking were associated with a significantly higher risk of dementia in patients with new-onset AF. Smoking cessation after AF diagnosis showed a lower risk of dementia compared to patients smoking persistently. These findings may support the promotion of smoking cessation to lower the risk of dementia in patients with new-onset AF. Funding Acknowledgement: Type of funding sources: None.